Electrode for electrolysis and hypochlorous acid generating apparatus

The electrolytic electrode design with a platinum-iridium oxide catalyst protected by a tantalum oxide layer addresses the degradation issue, maintaining long-term efficiency in hypochlorous acid generation.

JP2025014909APending Publication Date: 2025-01-30PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023117855
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

The degradation of catalyst activity over time in electrolytic electrodes is a significant issue, leading to reduced performance and efficiency in hypochlorous acid generation.

Method used

The electrolytic electrode design incorporates a metal substrate with a functional layer containing platinum and iridium oxide, separated by a metal oxide layer, and protected by a tantalum oxide layer, which maintains catalyst integrity and activity through a concentration gradient of tantalum atoms.

Benefits of technology

This configuration effectively suppresses the degradation of electrolytic performance, ensuring sustained efficiency in hypochlorous acid generation by protecting the catalyst layer from oxidation and wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014909000001_ABST
    Figure 2025014909000001_ABST
Patent Text Reader

Abstract

To provide an electrode for electrolysis that suppresses changes with time in characteristics of the electrode for electrolysis.SOLUTION: An electrode 1 for electrolysis comprises a metal substrate 2, a functional layer 7, and a metal oxide layer 3 interposed between the substrate 2 and the functional layer 7. The functional layer 7 includes: an intermediate layer 4 containing platinum and overlapping the metal oxide layer 3; a catalyst layer 5 containing platinum and iridium oxide and overlapping the intermediate layer 4; and a protective layer 6 containing at least one of tantalum and tantalum oxide and covering the intermediate layer 4 and the catalyst layer 5. The functional layer 7 has a concentration gradient of tantalum atoms such the concentration of tantalum atoms increases as a distance from the metal oxide layer 3 increases.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrode for electrolysis and a hypochlorous acid generation device, and more specifically, to an electrode for electrolysis containing iridium oxide and platinum and a hypochlorous acid generation device equipped with this electrode for electrolysis. [Background technology]

[0002] Patent Document 1 describes an electrode that is configured by providing an electrode catalyst layer via an intermediate layer on an electrode substrate made of titanium or a titanium alloy, and electrolyzes dilute salt water while repeatedly switching the polarity of the anode and cathode at a predetermined current density to generate chlorine. The electrode has an apparent density of 8 to 19 g / cm when the intermediate layer is provided on the substrate. 3 and an electrode catalyst layer composed of 3 to 10 mol % of iridium oxide, 35 to 65 mol % of tantalum oxide, and 25 to 62 mol % of platinum, calculated as metals. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-115188 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the case of an electrode for electrolysis, there is a problem of change over time in the characteristics due to a decrease in activity of the catalyst contained in the electrode for electrolysis, etc.

[0005] An object of the present disclosure is to provide an electrode for electrolysis capable of suppressing changes in characteristics over time, and a hypochlorous acid generating device including this electrode for electrolysis. [Means for solving the problem]

[0006] An electrolysis electrode according to one embodiment of the present disclosure includes a metal substrate, a functional layer, and a metal oxide layer interposed between the substrate and the functional layer. The functional layer includes an intermediate layer containing platinum and overlapping the metal oxide layer, a catalyst layer containing platinum and iridium oxide and overlapping the intermediate layer, and a protective layer containing at least one of tantalum and tantalum oxide and covering the intermediate layer and the catalyst layer. The functional layer has a concentration gradient of tantalum atoms, in which the concentration of tantalum atoms increases with increasing distance from the metal oxide layer.

[0007] A hypochlorous acid generator according to an embodiment of the present disclosure includes a container for containing salt water, and a first electrode and a second electrode disposed in the container so as to be in contact with the salt water. At least one of the first electrode and the second electrode includes the electrolysis electrode. Effect of the Invention

[0008] According to the present disclosure, it is possible to provide an electrode for electrolysis capable of suppressing changes in characteristics over time, and a hypochlorous acid generating device including this electrode for electrolysis. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of an electrode for electrolysis according to an embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a hypochlorous acid generating device according to an embodiment. [Diagram 3] FIG. 3 is a photograph taken with a differential scanning electron microscope of a cross section of an intermediate product during the production of the electrode for electrolysis in Example 1. [Figure 4] FIG. 4 is a photograph taken with a differential scanning electron microscope of a cross section of an intermediate product during the production of the electrode for electrolysis in Comparative Example 1. [Diagram 5] FIG. 5 is a graph showing the results of a composition analysis of the surface layer of the electrolysis electrode of Example 1 on the side having the functional layer, performed by X-ray photoelectron spectroscopy. [Figure 6] FIG. 6 is a graph showing the results of the durability test for Example 1, Comparative Example 1, and Reference Example. [Figure 7]FIG. 7 is a graph showing the results of the durability test for Example 1, Comparative Example 2, and the Reference Example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The following embodiments are merely a part of various embodiments of the present disclosure. In addition, the following embodiments can be modified in various ways depending on the design, etc., as long as the object of the present disclosure can be achieved. The figures referred to below are schematic diagrams, and the dimensional ratios of the components in the figures do not necessarily reflect the actual dimensional ratios. The action mechanisms of the embodiments shown below are estimated, and the present disclosure is not bound by the following explanation of the action mechanisms.

[0011] 1.Electrode for electrolysis The electrolysis electrode 1 of the embodiment includes a metal substrate 2, a functional layer 7, and a metal oxide layer 3 interposed between the substrate 2 and the functional layer 7. The functional layer 7 includes an intermediate layer 4, a catalyst layer 5, and a protective layer 6. The intermediate layer 4 contains platinum and overlaps the metal oxide layer 3. That is, the metal oxide layer 3 is interposed between the substrate and the intermediate layer 4. The catalyst layer 5 contains platinum and iridium oxide and overlaps the intermediate layer 4. That is, the intermediate layer 4 is interposed between the metal oxide layer 3 and the catalyst layer 5. The protective layer 6 contains at least one of tantalum and tantalum oxide, and covers the intermediate layer 4 and the catalyst layer 5. The functional layer 7 has a concentration gradient of tantalum atoms, in which the concentration of tantalum atoms increases with increasing distance from the metal oxide layer 3.

[0012] According to the embodiment, when the electrode for electrolysis 1 is used, the change over time in the characteristics of the electrode for electrolysis 1 can be suppressed. The reason for this is presumed to be as follows.

[0013] In the electrode for electrolysis 1, the catalytic layer 5 is held by the intermediate layer 4. In addition, since the metal oxide layer 3 is interposed between the metal substrate and the intermediate layer 4, oxidation of the metal substrate during use of the electrode for electrolysis 1 is suppressed. Therefore, it is possible to suppress the interface between the substrate and the intermediate layer 4 from becoming brittle due to oxides generated by the oxidation of the metal substrate. Therefore, it is possible to suppress the detachment of the catalytic layer 5 from the electrode for electrolysis 1. Furthermore, the catalytic layer 5 can also be protected by the protective layer 6 covering the catalytic layer 5. Furthermore, since there is a concentration gradient of tantalum atoms constituting the protective layer 6 in the functional layer 7, the catalytic layer 5 is sufficiently protected by the protective layer 6 near the surface layer of the functional layer 7. In addition, the presence of the concentration gradient of tantalum atoms means that the protective layer 6 and the catalytic layer 5 coexist deep inside the functional layer 7. Therefore, even if the surface layer of the protective layer 6 falls off or wears off over time, it is presumed that the protective layer 6 remains together with the catalytic layer 5 on the electrode for electrolysis 1, and therefore the catalytic layer 5 can be protected for a long period of time. Furthermore, even if the catalytic layer 5 is covered with the protective layer 6, the protective layer 6 is unlikely to inhibit the catalytic activity of the catalytic layer 5. Therefore, it is presumed that good electrolysis performance of the electrolysis electrode 1 and maintenance of the electrolysis performance can be achieved.

[0014] The electrolysis electrode 1 of the embodiment is used as an electrode in, for example, a hypochlorous acid generator. The hypochlorous acid generator includes a container in which salt water is placed, and a first electrode and a second electrode disposed in the container so as to be in contact with the salt water. At least one of the first electrode and the second electrode includes the electrolysis electrode 1. In particular, the electrolysis electrode 1 can be used as an anode. In this case, good chlorine production efficiency at the anode during electrolysis can be maintained for a long period of time. However, the use of the electrolysis electrode 1 of the embodiment is not limited to the above, and the electrolysis electrode 1 can be applied to various electrolyses using platinum and iridium oxide as catalysts.

[0015] The configuration of the electrode 1 for electrolysis will be described in more detail.

[0016] As described above, the substrate 2 is made of metal, that is, is made of a metal material. This makes the substrate 2 conductive. The metal constituting the substrate 2 includes at least one of titanium and a titanium alloy, for example. The titanium alloy includes at least one selected from the group consisting of a titanium-palladium alloy, a titanium-nickel-ruthenium alloy, a titanium-tantalum alloy, a titanium-aluminum alloy, and a titanium-aluminum-vanadium alloy, for example.

[0017] The substrate 2 is, for example, flat. The substrate 2 has a rectangular shape when viewed in the thickness direction of the substrate 2. The substrate 2 has a thickness of, for example, 100 μm or more and 2 mm or less, and is, for example, 500 μm. The substrate 2 has a size of, for example, 25 mm×60 mm in plan view. When the substrate 2 is flat, the substrate 2 has a first main surface 21 and a second main surface 22 opposite to the first main surface 21.

[0018] The metal oxide layer 3 is a layer containing a metal oxide. As described above, the metal oxide layer 3 overlaps the base material 2. The metal oxide layer 3 is formed so as to cover at least a part of the surface of the base material 2. The metal oxide layer 3 is formed so as to cover the base material 2 at least between the base material 2 and the intermediate layer 4. That is, the metal oxide layer 3 is interposed between the base material 2 and the intermediate layer 4. In the example shown in FIG. 1, the metal oxide layer 3 covers the entire first main surface 21 of the flat-plate-shaped base material 2.

[0019] The metal oxide in the metal oxide layer 3 may be an oxide of the same metal as that constituting the substrate 2, or may be an oxide of a metal different from that constituting the substrate 2.

[0020] It is more preferable that the metal oxide in the metal oxide layer 3 is an oxide of the same metal as the metal constituting the substrate 2. In this case, for example, if the substrate 2 contains titanium, the metal oxide layer 3 contains titanium oxide.

[0021] The thickness of the metal oxide layer 3 is preferably 0.1 μm or more and 5 μm or less. When the thickness of the metal oxide layer 3 is not uniform, the thickness is preferably 0.1 μm or more and 5 μm or less at any part of the metal oxide layer 3. If the thickness is 0.1 μm or more, oxidation of the base material 2 is further suppressed, and thus the detachment of the catalyst layer 5 from the electrode for electrolysis 1 can be further suppressed. If the thickness is 5 μm or less, the electrical conductivity of the electrode for electrolysis 1 is unlikely to be excessively inhibited by the metal oxide layer 3, and therefore good electrical conductivity of the electrode for electrolysis 1 can be maintained. This thickness is more preferably 0.5 μm or more. This thickness is more preferably 2 μm or less.

[0022] As described above, the intermediate layer 4 in the functional layer 7 contains platinum. Therefore, the intermediate layer 4 has high corrosion resistance to salt water and chlorine, and can increase the electrical conductivity of the entire electrolysis electrode 1. The intermediate layer 4 is made of, for example, platinum, or a mixture of tantalum, platinum, and iridium.

[0023] The intermediate layer 4 is overlaid on the metal oxide layer 3. Therefore, the electrode for electrolysis 1 has an interface between the metal oxide layer 3 and the intermediate layer 4.

[0024] The thickness of the intermediate layer 4 is, for example, not less than 0.3 μm and not more than 5 μm, and is, for example, 0.6 μm.

[0025] 1, the intermediate layer 4 may be separated into multiple layers on the metal oxide layer 3. That is, the intermediate layer 4 may include multiple layers distributed in an island shape on the metal oxide layer 3. Alternatively, the intermediate layer 4 may be a single, unseparated layer.

[0026] The intermediate layer 4 may be a porous layer. In this case, for example, the intermediate layer 4 may be a sintered body of platinum particles, and may be a porous layer in which pores are formed in the gaps between the platinum particles.

[0027] The catalytic layer 5 is overlaid on the intermediate layer 4. The electrolysis electrode 1 has an interface between the catalytic layer 5 and the intermediate layer 4. That is, the intermediate layer 4 is interposed between the catalytic layer 5 and the metal oxide layer 3.

[0028] The catalyst layer 5 includes platinum and iridium oxide. The catalyst layer 5 may be porous. In this case, the catalyst layer 5 may be a porous layer formed by, for example, assembling a plurality of particles and forming pores between the particles. Each of the plurality of particles includes, for example, platinum particles and iridium oxide particles, and, for example, a plurality of iridium oxide particles are bonded to one platinum particle. In the catalyst layer 5, the iridium oxide is dispersed by platinum. The iridium oxide can function as a catalyst for generating chlorine. The catalyst layer 5 may include iridium in addition to platinum and iridium oxide. In this case, the iridium particles may be bonded to the platinum particles in addition to the iridium oxide particles. In the catalyst layer 5, the platinum particles may be bonded to each other. The structure of the catalyst layer 5 is not limited to the above.

[0029] When the composition of the catalyst layer 5 is analyzed by X-ray photoelectron spectroscopy (XPS), the carbon concentration in the catalyst layer 5 is preferably less than the detection limit (0.1 atom %).

[0030] 1, when the intermediate layer 4 includes a plurality of layers distributed in an island pattern on the metal oxide layer 3, the catalyst layer 5 may include a plurality of layers overlapping each of the plurality of layers included in the intermediate layer 4. When the intermediate layer 4 is a single unseparated layer, the catalyst layer 5 may be a single unseparated layer overlapping the intermediate layer 4, or may include a plurality of layers distributed in an island pattern on the intermediate layer 4.

[0031] The catalyst layer 5 has a thickness of, for example, 0.1 μm or more and 10 μm or less.

[0032] As described above, the protective layer 6 contains at least one of tantalum and tantalum oxide. The protective layer 6 can suppress the elution of iridium oxide from the catalyst layer 5. Therefore, the protective layer 6 can protect the catalyst layer 5.

[0033] 1, when the intermediate layer 4 includes a plurality of layers distributed in an island shape on the metal oxide layer 3, and when the catalytic layer 5 includes a plurality of layers overlapping the plurality of layers included in the intermediate layer 4, the protective layer 6 is formed so as to cover the plurality of layers included in the intermediate layer 4 and the plurality of layers included in the catalytic layer 5 at the same time. That is, the protective layer 6 is formed so as to have a portion overlapping the surface of the plurality of layers included in the catalytic layer 5 opposite to the metal oxide layer 3, a portion that is inserted between the plurality of layers included in the catalytic layer 5, and a portion that is inserted between the plurality of layers included in the intermediate layer 4. Furthermore, when the catalytic layer 5 is porous, the protective layer 6 has a portion that is inserted into the pores of the catalytic layer 5, and when the intermediate layer 4 is porous, the protective layer 6 has a portion that is inserted into the pores in the intermediate layer 4.

[0034] In the embodiment, since the protective layer 6 has the above structure, a concentration gradient of tantalum atoms can exist in the functional layer 7, in which the concentration of tantalum atoms increases with increasing distance from the metal oxide layer 3.

[0035] In addition, when the intermediate layer 4 consists of only one layer and the catalytic layer 5 also consists of only one layer overlapping the intermediate layer 4, for example, the protective layer 6 is formed so as to overlap the surface of the catalytic layer 5 opposite the metal oxide layer 3. In this case as well, when the catalytic layer 5 is porous, the protective layer 6 may have a portion that penetrates into the pores of the catalytic layer 5, and when the intermediate layer 4 is porous, the protective layer 6 may have a portion that penetrates into the pores in the intermediate layer 4. This may cause a concentration gradient of tantalum atoms in the functional layer 7.

[0036] In the functional layer 7, the concentration of tantalum atoms on the surface in contact with the metal oxide layer 3 is preferably half or less of the concentration of tantalum atoms on the surface opposite to the surface in contact with the metal oxide layer 3. In other words, the concentration of tantalum atoms on the surface opposite to the surface in contact with the metal oxide layer 3 is preferably at least twice the concentration of tantalum atoms on the surface in contact with the metal oxide layer 3. In this case, good electrolysis performance of the electrolysis electrode 1 can be maintained for a longer period of time.

[0037] The concentration of tantalum atoms in the functional layer 7 is a concentration obtained from the results of an atomic composition analysis of the functional layer 7 by X-ray photoelectron spectroscopy (XPS).

[0038] 2. Manufacturing method of electrodes for electrolysis The following describes a method for producing the electrode for electrolysis 1. The electrode for electrolysis 1 of the embodiment is not limited to those produced by the following production method.

[0039] First, the base material, the material for the intermediate layer 4 (hereinafter referred to as the first material), the material for the catalyst layer 5 (hereinafter referred to as the second material), and the material for the protective layer 6 (hereinafter referred to as the third material) are prepared.

[0040] The base material is made of the same material as the substrate 2. For example, if the substrate 2 is made of titanium, the base material is also made of titanium.

[0041] The first material is, for example, a paste containing platinum particles or an organometallic compound containing platinum, a resin binder, and a solvent.

[0042] The second material is a solution containing a platinum compound and an iridium compound that are the source of the catalyst layer 5. More specifically, the second material is, for example, a solution in which a platinum compound and an iridium compound are dissolved in a solvent. The solvent is, for example, a liquid in which ethylene glycol monoethyl ether, hydrochloric acid, and ethanol are mixed. The platinum compound is, for example, chloroplatinic acid, but is not limited to this, and may be, for example, platinum chloride or the like. The chloroplatinic acid is, for example, hexachloroplatinic (IV) acid n-hydrate. The iridium compound is, for example, chloroiridic acid, but is not limited to this, and may be, for example, iridium chloride or iridium nitrate. The chloroiridic acid is, for example, hexachloroiridic (IV) acid n-hydrate. The metal concentration of the second material (the total concentration of platinum and iridium) is, for example, 10 to 50 mg / mL.

[0043] The third material is, for example, a solution in which a tantalum compound is dissolved in a solvent. The solvent is, for example, a liquid in which ethylene glycol monoethyl ether, hydrochloric acid, and ethanol are mixed. The tantalum compound is, for example, tantalum chloride, but is not limited thereto and may be, for example, tantalum ethoxide, etc. The metal concentration (tantalum concentration) of the third material is, for example, 50 mg / L.

[0044] The first material is applied onto the base material by a suitable method such as screen printing to form a coating film. The coating film is heated to volatilize the solvent to form a dry film. The heating temperature is, for example, 200°C or higher and 300°C or lower.

[0045] Next, the dried film of the first material and the raw material are fired under an air atmosphere. The heating temperature during firing is, for example, 650°C to 1000°C, for example, 800°C. The heating time during firing is, for example, 5 minutes to 180 minutes, for example, 10 minutes. As a result, the resin binder is removed from the dried film and the platinum particles are sintered to produce the intermediate layer 4. In addition, the surface layer of the raw material is oxidized during this firing. As a result, the oxidized part of the raw material becomes the metal oxide layer 3, and the non-oxidized part becomes the base material 2. The intermediate layer 4 is formed to be porous, and therefore the part of the raw material in contact with the intermediate layer 4 is also oxidized to form the metal oxide layer 3. Therefore, the metal oxide layer 3 overlapping the base material 2 and the intermediate layer 4 overlapping the metal oxide layer 3 are produced.

[0046] Next, the second material is applied onto the intermediate layer 4 and then dried to prepare a dry film. If necessary, the application and drying of the second material are repeated multiple times to adjust the thickness of the dry film, thereby adjusting the thickness of the catalyst layer 5. The heating temperature when drying the second material is, for example, 100°C or higher and 400°C or lower, and is, for example, 220°C. The heating time when drying the second material is, for example, 5 minutes or higher and 15 minutes or lower, and is, for example, 10 minutes. The application and drying of the second material are repeated, for example, 4 to 8 times.

[0047] Next, the dried film of the second material is fired to produce the catalyst layer 5. The heating temperature during firing is, for example, 300° C. to 600° C., and one example is 560° C. The heating time during firing is, for example, 5 minutes to 20 minutes, and one example is 10 minutes.

[0048] Next, a third material is applied so as to cover the intermediate layer 4 and the catalyst layer 5, and then dried to prepare a dry film. If necessary, the application and drying of the third material are repeated multiple times to adjust the thickness of the dry film, and thereby adjust the thickness of the protective layer 6. The heating temperature when drying the third material is, for example, 100°C or higher and 400°C or lower, and is, for example, 220°C. The heating time when drying the third material is, for example, 5 minutes or higher and 15 minutes or lower, and is, for example, 10 minutes. The application and drying of the third material are repeated, for example, 2 to 6 times.

[0049] Next, the dried film of the third material is baked to produce the protective layer 6. The heating temperature during baking is, for example, 500° C. to 600° C., and one example is 560° C. The heating time during baking is, for example, 5 minutes to 20 minutes, and one example is 10 minutes.

[0050] In this manufacturing method, when the intermediate layer 4 and the catalyst layer 5 are porous, applying the third material so as to cover the intermediate layer 4 and the catalyst layer 5 causes the third material to penetrate into the pores of the intermediate layer 4 and the pores of the catalyst layer 5. For this reason, the dry film of the third material includes a portion that penetrates into the pores of the intermediate layer 4 and a portion that penetrates into the pores of the catalyst layer 5, and the catalyst layer 5 produced by firing the dry film of the third material also includes a portion that penetrates into the pores of the intermediate layer 4 and a portion that penetrates into the pores of the catalyst layer 5.

[0051] 3. Hypochlorous Acid Generator The hypochlorous acid generator 100 includes a container 110 (aqueous sodium chloride solution) for containing salt water 112, and a first electrode 101A and a second electrode 101B disposed in the container 110 so as to be in contact with the salt water 112. In the hypochlorous acid generator 100, both the first electrode 101A and the second electrode 101B include the electrode for electrolysis 1, but it is sufficient that at least one of the first electrode 101A and the second electrode 101B includes the electrode for electrolysis 1.

[0052] The hypochlorous acid generator 100 further includes a main body case 102 having, for example, a rectangular box shape. The main body case 102 includes four side walls, an upper wall, and a bottom wall. In the main body case 102, one of a pair of two side walls facing each other among the four side walls has an air inlet 103, and the upper wall has an outlet 104 for blowing out air containing hypochlorous acid. In FIG. 2, the flow path 105 of the air sucked in from the inlet 103 and blown out from the outlet 104 is shown by an outlined arrow. The container 110 is disposed in the main body case 102 at the lower part of the main body case 102. The container 110 is a tray (a container without a lid). The hypochlorous acid generator 100 further includes a water supply tank 108 disposed in the main body case 102. The water supply tank 108 supplies water W1 in the water supply tank 108 to the container 110. The container 110 and the water tank 108 are detachably attached to the main body case 102 .

[0053] In addition, the hypochlorous acid generator 100 further includes an operation switch for instructing the start and stop of operation of the hypochlorous acid generator 100. The operation switch is disposed on the upper wall of the main body case 102, for example.

[0054] The hypochlorous acid generator 100 further includes a blower 106 that blows air from the inlet 103 toward the outlet 104, and a filter 107. The filter 107 is a rotatable cylindrical filter that can be permeated with electrolytic water containing hypochlorous acid to bring the electrolytic water into contact with the air passing through.

[0055] The blower 106 is disposed inside the main body case 102 at an upper portion of the main body case 102. The blower 106 includes, for example, a sirocco fan.

[0056] The water supply tank 108 is attached to the container 110. The water supply tank 108 includes an opening for water supply and an on-off valve unit that opens and closes the opening. When the water supply tank 108 is attached to the container 110, the on-off valve unit of the water supply tank 108 opens the opening, and the water W1 in the water supply tank 108 is supplied to the container 110. In the hypochlorous acid generator 100, when the opening of the water supply tank 108 is submerged in the water in the container 110, air cannot enter the water supply tank 108, and the on-off valve unit is closed by the gravity of the water W1 in the water supply tank 108, and the water W1 in the water supply tank 108 is no longer supplied to the container 110.

[0057] In the hypochlorous acid generator 100, an electrolysis auxiliary (for example, sodium chloride in tablet form) is added to the water in the container 110, whereby the electrolysis auxiliary dissolves and salt water (aqueous sodium chloride solution) is generated in the container 110.

[0058] Filter 107 is disposed in the lower portion of main body case 102 such that a portion of filter 107 is immersed in the liquid in container 110. Filter 107 is cylindrical, and rotates about the central axis of cylindrical filter 107 so that the portion immersed in the liquid in container 110 changes. Filter 107 is rotated by a motor. Filter 107 is capable of retaining electrolytic water generated from salt water 112 in container 110, and is also capable of passing air.

[0059] In addition, the hypochlorous acid generating device 100 further includes a water level sensor 109 that is disposed in the container 110 and detects the water level or saltwater level in the container 110, or drought.

[0060] The hypochlorous acid generating device 100 further includes a control device 114 for controlling the operation of the hypochlorous acid generating device 100, and a humidity sensor 113. The control device 114 is connected to an operation switch, a water level sensor 109, and a humidity sensor 113. The control device 114 is also connected to a motor for rotating the filter 107, a blower 106, a first electrode 101A, and a second electrode 101B. The control device 114 controls the filter 107, the blower 106, the first electrode 101A, and the second electrode 101B based on signals from the operation switch, the water level sensor 109, the humidity sensor 113, and the like. The control device 114 controls the voltage applied between the first electrode 101A and the second electrode 101B. As a result, the hypochlorous acid generating device 100 can generate electrolyzed water containing hypochlorous acid by electrolyzing salt water. In the hypochlorous acid generating device 100, electrolytic water is soaked into the filter 107, and then air is blown by the blower 106, so that the air that has come into contact with the electrolytic water through the filter 107 can be blown out from the outlet 104. The control device 114 includes, for example, a computer system. The computer system is mainly composed of a processor and a memory as hardware. The function of the control device 114 is realized by the processor executing a program recorded in the memory of the computer system. The program may be pre-recorded in the memory of the computer system, may be provided through an electric communication line, or may be recorded and provided in a non-transitory recording medium such as a memory card, an optical disk, or a hard disk drive that can be read by the computer system. The processor of the computer system is composed of one or more electronic circuits including a semiconductor integrated circuit (IC) or a large-scale integrated circuit (LSI). The integrated circuits such as IC or LSI mentioned here are called by different names depending on the degree of integration, and include integrated circuits called system LSI, VLSI (Very Large Scale Integration), or ULSI (Ultra Large Scale Integration).Furthermore, a field-programmable gate array (FPGA) that is programmed after the manufacture of an LSI, or a logic device that allows reconfiguration of the connection relationship within the LSI or reconfiguration of the circuit partition within the LSI, can also be employed as a processor. The electronic circuits may be integrated into one chip, or may be distributed among multiple chips. The chips may be integrated into one device, or may be distributed among multiple devices. The computer system referred to here includes a microcontroller having one or more processors and one or more memories. Thus, the microcontroller is also composed of one or more electronic circuits including a semiconductor integrated circuit or a large-scale integrated circuit.

[0061] 4. Variations The embodiment is merely one of various embodiments of the present disclosure. The embodiment can be modified in various ways depending on the design and the like as long as the object of the present disclosure can be achieved.

[0062] For example, the planar shape of the base material 2 is not limited to a rectangular shape, and may be any shape, such as a square shape or a circular shape.

[0063] The substrate 2 is not limited to a flat plate shape, and may be in any other suitable shape, such as a rod shape or a honeycomb shape.

[0064] In the embodiment, the electrode 1 for electrolysis comprises a metal oxide layer 3 overlapping the entire first main surface 21 of the substrate 2 and a functional layer 7 overlapping the metal oxide layer 3, but the metal oxide layer 3 may overlap only a portion of the first main surface 21, and the functional layer 7 may overlap the metal oxide layer 3. The electrode 1 for electrolysis may also comprise a metal oxide layer 3 overlapping the first main surface 21 of the substrate 2 and a functional layer 7 overlapping the metal oxide layer 3, and a metal oxide layer 3 overlapping the second main surface 22 of the substrate 2 and a functional layer 7 overlapping the metal oxide layer 3.

[0065] In the embodiment, when the electrode 1 for electrolysis is manufactured, the dry film of the first material and the raw material are fired to form the intermediate layer 4 from the dry film of the first material, and the surface layer of the raw material is oxidized to form the metal oxide layer 3. However, for example, the surface layer of the raw material may first be oxidized to form the metal oxide layer 3, and then a dry film of the first material may be formed on the metal oxide layer 3, and the dry film may then be fired to form the intermediate layer 4. In this case, in order to oxidize the surface layer of the raw material, the raw material is fired, for example, in an air atmosphere. Alternatively, the surface layer of the raw material may be oxidized by anodization. EXAMPLES

[0066] Specific examples of the present disclosure will be described below. Note that the present disclosure is not limited to the following examples.

[0067] 1. Evaluation of metal oxide layer (1) Example 1 A titanium plate measuring 26 mm x 60 mm x 0.5 mm was prepared as the raw material.

[0068] The first material, which is the material for the intermediate layer, was prepared by mixing 70 parts by mass of a paste containing platinum particles (manufactured by Tanaka Kikinzoku Co., Ltd., product name TR-7091T) and 30 parts by mass of a solvent (diluent manufactured by Tanaka Kikinzoku Co., Ltd., product name TMS-8).

[0069] The second material, which is the material of the catalyst layer, was prepared by mixing a platinum compound, hexachloroplatinic (IV) acid hexahydrate manufactured by Fuji Film Wako Pure Chemical Industries, Ltd., an iridium compound, hexachloroiridic (IV) acid n-hydrate manufactured by Fuji Film Wako Pure Chemical Industries, Ltd., and a mixed solvent containing ethanol and ethylene glycol monobutyl ether in a mass ratio of 5: 4 as a solvent. In the second material, the mass ratio Pt:Ir of the platinum metal equivalent amount of the platinum compound to the iridium metal equivalent amount of the iridium compound was 8: 11, and the total metal equivalent concentration of the platinum compound and the iridium compound was 50 mg / mL.

[0070] The third material, which is the material of the protective layer, was prepared by mixing tantalum chloride (V), which is a tantalum compound, with a mixed solvent containing ethanol and ethylene glycol monobutyl ether in a mass ratio of 5: 4. The concentration of the tantalum compound in the third material, converted to metallic tantalum, was 25 mg / mL.

[0071] The first material was applied to one side of the base material by screen printing to create a coating film distributed in an island shape, and the coating film was baked at 800°C for 10 minutes in an air atmosphere.

[0072] A photograph of the cross section of the raw material after this treatment taken with a differential scanning electron microscope is shown in Figure 3. From Figure 3, it can be seen that the surface layer of the raw material was oxidized to form a metal oxide layer, the thickness of this metal oxide layer was 0.1 μm to 5 μm, and an intermediate layer separated into multiple layers distributed in an island shape was formed on the metal oxide layer.

[0073] The second material was applied onto the intermediate layer, and then heated at 220°C for 10 minutes. This process was repeated eight times to produce a dry film of the second material on the intermediate layer. This dry film of the second material was then heated at 560°C for 10 minutes in an air atmosphere. This produced a catalyst layer on the intermediate layer.

[0074] Next, the third material was applied to cover the intermediate layer and the catalyst layer, and then the third material was heated at 220°C for 10 minutes. This was repeated twice to produce a dry film of the third material covering the intermediate layer and the catalyst layer. This dry film of the third material was heated at 560°C for 10 minutes in an air atmosphere. This produced a protective layer covering the intermediate layer and the catalyst layer.

[0075] In this manner, an electrode for electrolysis was prepared.

[0076] (2) Comparative Example 1 As in Example 1, the original material, the first material, the second material, and the third material were prepared.

[0077] The first material was applied to one surface of the base material by screen printing to form a coating film, which was then baked at 800°C for 10 minutes in a vacuum atmosphere.

[0078] A photograph of the cross section of the raw material after this treatment taken with a differential scanning electron microscope is shown in Figure 4. From Figure 4, it can be seen that no metal oxide layer was formed on the surface of the raw material, and the intermediate layer was directly layered on top of the raw material.

[0079] The second material was applied onto the intermediate layer, and then heated at 220°C for 10 minutes. This process was repeated eight times to produce a dry film of the second material on the intermediate layer. This dry film of the second material was then heated at 560°C for 10 minutes in an air atmosphere. This produced a catalyst layer on the intermediate layer.

[0080] Next, the third material was applied to cover the intermediate layer and the catalyst layer, and then the third material was heated at 220°C for 10 minutes. This was repeated twice to produce a dry film of the third material covering the intermediate layer and the catalyst layer. This dry film of the third material was heated at 560°C for 10 minutes in an air atmosphere. This produced a protective layer covering the intermediate layer and the catalyst layer.

[0081] In this manner, an electrode for electrolysis was prepared.

[0082] (3) Reference example The raw material was ultrasonically cleaned with acetone for 10 minutes, treated with an 8% by mass aqueous solution of hydrofluoric acid at 20°C for 2 minutes, treated with a 60% by mass aqueous solution of sulfuric acid at 120°C for 3 minutes, sprayed with cold water in a nitrogen atmosphere, immersed in a 0.3% by mass aqueous solution of hydrofluoric acid at 20°C for 2 minutes, and rinsed with water.

[0083] One surface of the base material was subjected to electrolytic plating to form a platinum coating layer (intermediate layer). For the plating, a platinum plating bath was used in which dinitrodiammine platinum was dissolved in a sulfuric acid solution, with a platinum concentration of 5 g / L, a pH of about 2, and a temperature of 50°C. The treatment conditions were a current density of 30 mA / cm. 2 , and processing time is 6 minutes.

[0084] A butanol solution of chloroiridic acid with an iridium concentration of 100g / L, a butanol solution of tantalum ethoxide with a tantalum concentration of 200g / L, and a butanol solution of chloroplatinic acid with a platinum concentration of 70g / L were mixed so that the composition ratio of Ir:Ta:Pt was 5:40:55 in terms of metal conversion, and the total concentration of each metal component was 75g / L, and diluted with butanol to prepare an electrode catalyst layer coating solution. 250μL of the coating solution was weighed out with a pipette and applied to the platinum coating layer, and the platinum coating layer was tilted with tweezers to spread the solution over the entire surface of the platinum coating layer, and then dried at room temperature and baked in air at 530℃ for 10 minutes. This coating, drying, and baking process was repeated four times. This produced a catalyst layer.

[0085] In this manner, an electrode for electrolysis was prepared.

[0086] (4) Atomic composition evaluation The composition of the surface layer of the electrode for electrolysis in Example 1 on the side having the functional layer was analyzed by X-ray photoelectron spectroscopy (XPS). Specifically, the measurement was performed under the following conditions using an X-ray photoelectron spectrometer, Quantera SXM, manufactured by ULVAC-PHI.

[0087] X-ray: Monochrome Al Kα, beam diameter 100 μmφ, power 15 kV, 25 W.

[0088] Etching conditions: acceleration voltage 2 kV, raster size 1 mm x 1 mm, etching speed 14 nm / min in SiO2 equivalent.

[0089] The results are shown in the graph in Figure 5. The vertical axis indicates atomic concentration, and the horizontal axis indicates the depth in the thickness direction of the electrolysis electrode, with the surface of the functional layer being 0 (μm). The graph shows the measurement results of the atomic concentrations of carbon (C), platinum (Pt), oxygen (O), iridium (Ir), tantalum (Ta), and titanium (Ti).

[0090] In this result, the location where the concentration value of titanium (Ti) rises can be determined to be the interface between the metal oxide layer and the functional layer. This interface is shown in the graph by a vertical line. That is, the left side of the line is the functional layer, and the right side is the metal oxide layer and the substrate. According to this result, platinum, titanium, and tantalum are also contained in the metal oxide layer and the substrate, which is presumably due to the influence of knocking that occurs during measurement by the XPS method. In the embodiment, the atomic concentration is specified based on the measurement result by XPS, including the influence of knocking.

[0091] These results confirm that there is a concentration gradient of tantalum atoms in the functional layer, such that the concentration of tantalum atoms increases the further away from the metal oxide layer, and that the concentration of tantalum atoms on the surface of the functional layer that contacts the metal oxide layer is less than half the concentration of tantalum atoms on the surface opposite to the surface that contacts the metal oxide layer.

[0092] (5) Evaluation test a. Durability test In each of Example 1, Comparative Example 1, and Reference Example, two electrodes for electrolysis were prepared. The two electrodes for electrolysis were arranged facing each other with a gap of 4 mm between them. The two electrodes for electrolysis were immersed in a liquid flow of an electrolytic solution. The electrolytic solution was an aqueous sodium chloride solution with a concentration of 0.017 mol / L, and the liquid flow rate of the electrolytic solution was 2.0 L / min. In this state, a current density of 25 mA / cm at each electrode for electrolysis was applied between the two electrodes for electrolysis. 2 A voltage was applied while switching the polarity every 180 seconds so as to obtain the following:

[0093] b. Electrolysis performance test During the above durability test, the following electrolysis performance test was carried out several times at intervals on the electrolysis electrodes subjected to the durability test.

[0094] An electrolyte solution for evaluation was prepared by dissolving 0.9 g of sodium chloride in 1500 mL of ion-exchanged water. The electrolyte solution was placed in an electrolytic cell, and two electrodes for electrolysis were immersed in the electrolyte solution while facing each other with a gap of 4 mm between them.

[0095] In this state, between the two electrolysis electrodes, the current density at each electrode was 25 mA / cm 2 A voltage was applied for 3 minutes so that the voltage was 0.01 V. The electrolyte was then stirred at 730 rpm with a magnetic stirrer without applying a voltage. The above operation was repeated four times while alternately switching the polarity of the voltage.

[0096] Next, a portion of the electrolyte was extracted as a sample, and the sodium chloride concentration of this sample was measured using a Chlorine Meter RC50T manufactured by Bionics Instruments Co., Ltd. From the results, the amount of chlorine generated per volume of electrolyte in the electrolysis electrode (unit: mgL -1 ) was calculated.

[0097] c.Evaluation In the durability test, the voltage applied to the electrolysis electrodes exceeds 15 V, or the amount of chlorine generated in the electrolysis performance test is 3.0 mg / L. -1 When the electrolysis electrode reached or exceeded the limit, the life of the electrode for electrolysis was deemed to have expired, and the life of the electrode for electrolysis was evaluated.

[0098] 6 is a graph showing the change over time in the evaluation results of the amount of chlorine generated, where "A" shows the results for Example 1, "B" for Comparative Example 1, and "C" for the Reference Example. In addition, "X" is given to the evaluation at the point when the lifespan is considered to have expired.

[0099] These results confirm that the good performance of the electrode for electrolysis is sustained longer by interposing a metal oxide layer between the substrate and the intermediate layer as in Example 1, compared to the cases where no metal oxide layer is interposed between the substrate and the intermediate layer as in Comparative Example 1 and Reference Example.

[0100] 2. Evaluation of the protective layer (1) Comparative Example 2 An electrode for electrolysis was prepared in the same manner as in Example 1, except that no protective layer was prepared.

[0101] (2) Evaluation test In Comparative Example 2, the same durability test and electrolytic performance test as in "1. Evaluation of metal oxide layer" were carried out.

[0102] Fig. 7 is a graph showing the change over time in the evaluation results of the amount of chlorine generated, with "B" showing the results for Comparative Example 2. Additionally, "A" shows the results for Example 1 in "1. Evaluation of the metal oxide layer," and "C" shows the results for the Reference Example. Additionally, "X" is given to the evaluation at the point when the lifespan is considered to have expired.

[0103] This result confirms that, compared to the case where no protective layer was prepared as in Comparative Example 2, the excellent performance of the electrode for electrolysis was sustained longer by preparing a protective layer as in Example 1.

[0104] [Aspects] The electrolysis electrode (1) of the first embodiment comprises a metal substrate (2), a functional layer (7), and a metal oxide layer (3) interposed between the substrate (2) and the functional layer (7). The functional layer (7) comprises an intermediate layer (4) containing platinum and overlapping the metal oxide layer (3), a catalyst layer (5) containing platinum and iridium oxide and overlapping the intermediate layer (4), and a protective layer (6) containing at least one of tantalum and tantalum oxide and covering the intermediate layer (4) and the catalyst layer (5). The functional layer (7) has a concentration gradient of tantalum atoms, in which the concentration of tantalum atoms increases with increasing distance from the metal oxide layer (3).

[0105] According to this embodiment, the change over time in the characteristics of the electrode for electrolysis (1) can be suppressed.

[0106] In the second embodiment, the thickness of the metal oxide layer (3) in the first embodiment is 0.1 μm or more and 5 μm or less.

[0107] According to this embodiment, the change over time in the characteristics of the electrode for electrolysis (1) can be further suppressed.

[0108] In the third aspect, in the first or second aspect, the concentration of tantalum atoms in the surface of the functional layer (7) that contacts the metal oxide layer (3) is less than half of the concentration of tantalum atoms in the surface opposite the surface that contacts the metal oxide layer (3).

[0109] According to this embodiment, the change over time in the characteristics of the electrode for electrolysis (1) can be further suppressed.

[0110] A hypochlorous acid generator (100) according to a fourth aspect includes a container (110) for containing salt water, and a first electrode (101A) and a second electrode (101B) disposed in the container (110) so as to be in contact with the salt water. At least one of the first electrode (101A) and the second electrode (101B) includes the electrode for electrolysis (1) according to any one of the first to third aspects.

[0111] According to this embodiment, the deterioration over time of the characteristics of the electrodes in the hypochlorous acid generator (100) can be suppressed. [Explanation of symbols]

[0112] 1 Electrode for electrolysis 2 Base material 3 Metal oxide layer 4. Middle Tier 5 Catalyst layer 6 Protective layer 7 Functional Layers 100 Hypochlorous Acid Generator 101A 1st electrode 101B 2nd electrode 110 Container

Claims

1. A metal substrate; A functional layer; A metal oxide layer is provided between the substrate and the functional layer, the functional layer includes an intermediate layer containing platinum and overlapping the metal oxide layer, a catalyst layer containing platinum and iridium oxide and overlapping the intermediate layer, and a protective layer containing at least one of tantalum and tantalum oxide and covering the intermediate layer and the catalyst layer; The functional layer has a concentration gradient of tantalum atoms, in which the concentration of tantalum atoms increases with increasing distance from the metal oxide layer. Electrode for electrolysis.

2. The thickness of the metal oxide layer is 0.1 μm or more and 5 μm or less. The electrode for electrolysis according to claim 1 .

3. a concentration of tantalum atoms in a surface of the functional layer in contact with the metal oxide layer is half or less of a concentration of tantalum atoms in a surface opposite to the surface in contact with the metal oxide layer; The electrode for electrolysis according to claim 1 .

4. A container for holding salt water; a first electrode and a second electrode disposed in the container so as to be in contact with the salt water; At least one of the first electrode and the second electrode includes the electrode for electrolysis according to any one of claims 1 to 3. Hypochlorous acid generator.

Citation Information

Patent Citations

  • Electrode for generating chlorine

    JP2017115188A